FORMULASI DELIK MABUK DALAM KUHP BARU (UU NO. 1 TAHUN 2023) DAN QANUN ACEH NOMOR 6 TAHUN 2014: SUATU KAJIAN KOMPARATIF - Qothrun Nada Tsabita Qolbiyah; Desi Kirana; Arif Syawaluddin Lubis; Dafhin Attallah; Ratu Zahwah Shopandi; Sevia Nurhayati; Riyo Fitriyan Nugroho; Syahrul Anwar (JOSH: Journal of Sharia, 2026)
This research analyzes the formulation of criminal offenses related to intoxication under Law No. 1 of 2023 on the Indonesian Penal Code (KUHP) and the concept of jarimah syurb  al-khamr in Aceh Qanun No. 6 of 2014 within Islamic criminal law (fiqh jinayah). This normative legal study employs statutory, conceptual, and comparative approaches through library research and qualitative-descriptive analysis. The findings reveal a fundamental divergence between the two legal systems. The KUHP adopts a public order approach that criminalizes intoxication only when it causes public disturbance or endangers others, whereas the Aceh Qanun criminalizes the consumption of alcohol itself based on a moral-religious paradigm. These differences extend to the elements of the offense, evidentiary standards, and types of sanctions, fines and imprisonment under the KUHP versus flogging under the Qanun Jinayat. Nevertheless, both systems share the objective of protecting public welfare and reject the elimination of criminal responsibility for intoxicated offenders through the doctrine of actio libera in causa. This study concludes that these differences reflect weak legal pluralism and divergent punitive paradigms rather than an absolute contradiction. Therefore, national criminal law policy should consider integrating preventive principles from Islamic criminal law through stronger non-penal measures while adhering to human rights principles and the national legal framework.